Black gathering : art, ecology, ungiven life - Cervenak, Sarah Jane, 1975- (Black outdoors., 2021)
"In Black Gathering, Sarah Jane Cervenak engages post-1970s Black artists and writers who, through language, image, and form, create alternate environments for Black people and earth to come together without interruption or regulation. Drawing on Black feminist theory, critical theories of ecology and ecoaesthetics, and theories of Black aesthetics, Cervenak engages Black artistic enactments of ecology and ungiven life. She thinks particularly about how Black artists and writers, like Gayl Jones and Clementine Hunter, enact spaces of gathering for the besieged to come together without regulation. Moreover, she attends to the significance of Black artists' gatherings as praxis, as practice without the interruptions of imposed category or imposed relation"--Publisher's description.